Characteristics recurrence pattern of cholangiolocellular carcinoma as intrahepatic bile duct tumor growth following curative resection: a case report - Keishi Hakoda; Tomoyuki Abe; Hironobu Amano; Tomoyuki Minami; Tsuyoshi Kobayashi; Keiji Hanada; Kenji Nishida; Shuji Yonehara; Masahiro Nakahara; Hideki Ohdan; Toshio Noriyuki (Surgical Case Reports, 2019)
Abstract Background Cholangiolocellular carcinoma (CoCC) is a rare primary liver tumor that shows mass-forming growth in most cases. At present, no effective treatment for hepatic recurrence CoCC has been established. We present a case involving a patient with recurrent disease that showed an intraductal growth (IG type) pattern of recurrence. The patient was treated with repeat hepatectomy with bile duct reconstruction. Case presentation The patient was a 76-year-old man with a history of S8 subsegmentectomy for CoCC. At 8 months after surgery, tumor marker elevation was observed. Computed tomography revealed a tumor occupying the right hepatic duct (B5-8) to B4 and the junction of the cystic duct. Endoscopic retrograde cholangiopancreatography (ERCP) and a thrombus biopsy with peroral cholangioscopy (POCS) confirmed the recurrence of CoCC in the intrahepatic bile duct. Although extended right lobectomy with extrahepatic bile duct resection was the optimal curative procedure, it was thought that it would be difficult due to his poor liver function. However, a slow-glowing recurrent tumor blocked the posterior branch of the portal vein; thus, the right liver lobe gradually shrank, and the estimated remnant liver volume increased in response, allowing curative surgery to finally be performed. At 10 months after surgery, the patient is alive without recurrence. Conclusions We reported a case of IG-type recurrence in the bile duct, which is an unusual pattern of intrahepatic recurrence, after initial surgery for CoCC. A slow-growing recurrent tumor exerted similar effects to PVE, which allowed for curative surgery to be performed.